Risk of vertebral compression fractures in multiple myeloma patients: A finite-element study. Issue 2 (January 2017) - Anitha, D.; Thomas, Baum; Jan, Kirschke S.; Subburaj, Karupppasamy
Abstract : Abstract: The purpose of this study was to develop and validate a finite element (FE) model to predict vertebral bone strength in vitro using multidetector computed tomography (MDCT) images in multiple myeloma (MM) patients, to serve as a complementing tool to assess fracture risk. In addition, it also aims to differentiate MM patients with and without vertebral compression fractures (VCFs) by performing FE analysis on vertebra segments (T1–L5) obtained from in vivo routine MDCT imaging scans. MDCT-based FE models were developed from the in vitro vertebrae samples and were then applied to the in vivo vertebrae segments of MM patients (n = 4) after validation. Predicted fracture load using FE models correlated significantly with experimentally measured failure load ( r  = 0.85, P  < 0.001). Interestingly, an erratic behavior was observed in patients with fractures (n = 2) and a more gradual change in FE-predicted strength values in patients without fractures (n = 2). Severe geometric deformations were also observed in models that have already attained fractures. Since BMD is not a reliable parameter for fracture risk prediction in MM subjects, it is necessary to use advanced tools such as FE analysis to predict individual fracture risk. If peaks are observed between adjacent segments in an MM patient, it can be safe to conclude that the spine is experiencing regions of structural instability. Such an FE visualization may have therapeutic consequences to prevent MM associated vertebral fractures.